Presynaptic mechanisms of neuronal plasticity and their role in epilepsy - Meier, Jochen C.; Semtner, Marcus; Winkelmann, Aline; Wolfart, Jakob (Frontiers in Cellular Neuroscience, 2014)
Synaptic communication requires constant adjustments of pre- and postsynaptic efficacies. In addition to synaptic long term plasticity, the presynaptic machinery underlies homeostatic regulations which prevent out of range transmitter release. In this minireview we will discuss the relevance of selected presynaptic mechanisms to epilepsy including voltage- and ligand-gated ion channels as well as cannabinoid and adenosine receptor signaling.